"I can’t write": problems, factors, and recommendations - Gorospe, Joanne D.; Rayton, Ma. Imelda C. (Technium Social Sciences Journal, 2022)
Writing is a significant skill whose significance increases when it comes to writing in the English language which is used for global mediation of knowledge. This study explored the problems encountered by students who have difficulty in writing, the factors which could be reasons for these difficulties, and the possible solutions to overcome these. This made use of qualitative research design and employed phenomenological case study framework. After thematic analyses, it was found that the students encountered problems in writing specifically in syntax, grammar, and vocabulary. The students believed that lack of reading and writing practice, lack of ideas, and lack of self-confidence were the factors affecting their writing skills. To address the problems that they encountered in writing, the students recommended increased reading, writing practice, and teacher assistance.